Understanding Indonesian Organizational Culture through Hofstede Insights: A Comparison with Malaysia, Singapore, and Thailand - Rezkiawan Tantawi; Idham Masri Ishak; Near Anggreini Hesti Noviana; Miranda Botutihe; Fadel Hidayat (Jambura Science of Management, 2026)
Purpose: Despite having the largest population and human resources in the ASEAN region, Indonesia still lags in terms of productivity compared to countries such as Singapore, Thailand, and Malaysia. This fact highlights a fundamental issue that is not only technical and economic but also closely tied to the organizational culture embedded within the work system. The objective of this study is to analyze Indonesia’s organizational culture using the Hofstede Insights approach, supported by the Culture Compass as an analytical tool, and to compare Indonesia's condition with those of other Southeast Asian countries that exhibit high labor productivity.Design/Methodology/Approach: This study employs a descriptive quantitative method, supported by data obtained using an AI-based Culture Compass instrument, developed from Hofstede’s organizational culture indicators and calibrated to the local context.Findings: This study reveals that Indonesia's low labor productivity is closely linked to cultural factors, including high power distance, strong collectivism, short-term orientation, and low indulgence. Compared with Malaysia, Singapore, and Thailand, Indonesia’s organizational culture is less adaptive to contemporary work demands, thereby hindering innovation, leadership participation, and talent development. Strategic cultural transformation is essential to improve human capital competitiveness.